Investigating the efficiency of mixtures based on supercritical CO2 and lubricants by friction tests under conditions similar to the machining of Ti6Al4V - Koulekpa, Koffi Samuel; Benked-Dar, Chadi; Elias-Birembaux, Hélène; Rossi, Frédéric; Poulachon, Gérard (Frontiers in Manufacturing Technology, 2024)
New supercritical carbon dioxide (scCO 2 )based cutting fluids combining the cooling from scCO 2 and lubrication from various additives are investigated in this study. Selected components including ionic liquids, vegetable and mineral oils, water, and PEG, were introduced into supercritical CO 2 and tribological tests were performed on a CNC lathe to analyse their influence on Ti6Al4V / WC-Co contact. Forces and temperatures were recorded to compare the influence of the scCO 2 -lubricants mixtures, for future usage in machining. The analysis of apparent friction coefficient and sticking zone, showed noticeable decrease by ionic liquids when combined with scCO 2 at a speed of 100 m/min and 4 ml/min delivery flow rate. The other lubricants (water, PEG vegetable oils) performed similarly to standard mineral oil though less expensive, which could help in developing future low-cost yet effective cooling and lubrication methods for the machining industry.